2013
DOI: 10.1364/ao.52.0000e6
|View full text |Cite
|
Sign up to set email alerts
|

Size dependence of harvested BaTiO3 nanoparticles on the electro-optic and dielectric properties of ferroelectric liquid crystal nanocolloids

Abstract: The influence of the size of harvested barium titanate nanoparticles on the properties of ferroelectric liquid crystal (FLC) nanocolloids was investigated by electro-optical and dielectric methods. The spontaneous polarization and the switching time are decreased for the liquid crystalline nanocolloids compared to nondoped FLC mixtures of different dipole strengths; this dependence is stronger for small size particles (9 nm) and weaker for larger size particles (26 nm) by the same concentration in weight. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…6,[14][15][16][17][18][19][20][21][22] In addition to the size, the nanoparticle surface properties are also crucial for the manifestation of a well dispersed medium. Surface modification of NPs has been mainly been employed to achieve long-term stability of NPs in the LC medium and to smoothen director distortions around NPs, 23 thus reducing the cost of elastic energy.…”
Section: Reznikov Et Al Have Shown That a Low Concentration Of Ferromentioning
confidence: 99%
See 1 more Smart Citation
“…6,[14][15][16][17][18][19][20][21][22] In addition to the size, the nanoparticle surface properties are also crucial for the manifestation of a well dispersed medium. Surface modification of NPs has been mainly been employed to achieve long-term stability of NPs in the LC medium and to smoothen director distortions around NPs, 23 thus reducing the cost of elastic energy.…”
Section: Reznikov Et Al Have Shown That a Low Concentration Of Ferromentioning
confidence: 99%
“…This is often achieved by coating the surface with monomolecular organic materials, surfactants (stabiliser), or ligands. For instance, oleic acid, 7,10,17,20,21,[24][25][26][27] selenium docosane 28 and dodecylbenzenesulphonic acid 29,30 have been widely utilized for the coating of NPs.…”
Section: Reznikov Et Al Have Shown That a Low Concentration Of Ferromentioning
confidence: 99%
“…Rudzki et al investigated the influence of the size of harvested barium titanate nanoparticles on the properties of ferroelectric LCs nanocolloids by electro-optical and dielectric methods [76]. The spontaneous polarization and the switching time were found to decrease for the LC nanocolloids compared to nondoped ferroelectric LC mixtures of different dipole strengths.…”
Section: Properties Of Doped Ferroelectric Liquid Crystalsmentioning
confidence: 99%
“…[17] It has also been observed that the enhanced properties of doped LC also depend on the dopant synthesis method. Rudzki et al [18] have recently studied the effects of the size of harvested BaTiO 3 nanoparticles on the electro-optical and dielectric properties of FLC and reported the decrease in spontaneous polarization and switching time of doped FLC as compared to the pure FLC. In this paper, the effect of doping of two different particle sizes (5À10 and 50À60 nm) of same concentration of BaTiO 3 prepared by hydrothermal method in pure FLC ethyl 4 00 -((6-acetoxyhexyl)oxy)-2,2 0 ,2 00 ,3,3 0 ,6 00 -hexafluoro-5-hexyl-[1,1 0 :4 0 ,1 00 -terphenyl]-4-carboxylate compound with ethyl 4 00 -((6-acetoxyhexyl)oxy)-2,2 0 ,3,3 0 -tetrafluoro-5-hexyl-[1,1 0 :4 0 ,1 00 -terphenyl]-4-carboxylate(1:1) abbreviated as 6F 6 T have been studied.…”
Section: Introductionmentioning
confidence: 99%